In service teacher’ atttude towards bullying: empirical evidence from suburb and rural area in Indonesia - Syahruddin Mahmud; Nellitawati Nellitawati; Singgih Ginanjar; Tanya Beran (Jurnal Konseling dan Pendidikan, 2026)
Despite the increasing concern over school bullying in Indonesia, limited empirical studies have examined teachers’ attitudes toward bullying across different school contexts and professional statuses. This study aims to compare teachers’ attitudes toward school bullying based on school location (suburban and rural) and teacher certification status. A quantitative survey design was employed using the Teachers’ Attitudes About Bullying Questionnaire (TAABQ), administered to 75 in-service high school teachers in South Sulawesi Province, Indonesia. Participants were selected using purposive sampling. Data were analyzed using descriptive statistics and comparative analysis of mean scores across groups. The findings revealed four key dimensions of teachers’ attitudes: system commitment, teacher commitment, concern, and confidence. Overall, teachers demonstrated strong awareness of the negative impact of bullying and emphasized the need for school policies, parental involvement, and professional development programs. Certified teachers consistently reported higher scores across all dimensions compared to uncertified teachers. Similarly, teachers in suburban schools showed stronger commitment and concern, whereas teachers in rural schools reported relatively higher confidence in handling bullying incidents. These findings contribute theoretically to the literature on teacher responses to school bullying in developing-country contexts and provide practical implications for teacher professional development and anti-bullying policy interventions.